The impact of mercury use in the small-scale gold mining sector on women of reproductive age: a case study of Kadoma - Manga, Faith V. (Midlands State University, 2019)
The aim of the study was to analyse the impact of mercury use in the small-scale gold mining sector on women of reproductive age in Kadoma, Zimbabwe. A mixed research design was used for this study, whereby both quantitative and qualitative data collection techniques were applied. Purposive sampling technique was used to determine a cohort of 85 respondents and data was collected through self-administered questionnaires, interviews with key respondents from Small Scale Miner`s Associations of Kadoma and Environmental Management Agency as well as direct field observations. Research findings showed that 63% of the women participating in gold mining activities are between the ages 25 and 35, 56% are married and 68% have household sizes of between 7 to 9 people. The findings also revealed that 40% of the women in the 30-35 year age group are exposed to mercury through amalgam making, 96% of the women in the 36-40 year age group exposed to mercury through amalgam burning while 33% are exposed to mercury through purifying mercury using nitric acid and others exposed to mercuric vapour due to their proximity to amalgam burning places. Strategies employed to reduce exposure to mercury include use of retorts and rotating of mining duties. Recommendations were made that the women of reproductive age should refrain from using mercury and adopt the use of other methods which reduce exposure to mercury like the “Kitchen Bowl” retort.